An assessment of user satisfaction on library services: a case studyof undergraduate Biology students at the University of Jaffna - Chandrasekar, K.; Murugathas, K. (Journal of the University Librarians Association of Sri Lanka, 2012)
The paper discusses the results of the user satisfaction survey conducted in the Jaffna University library among the undergraduates of general degree bioscience students in August 2010. The objectives of the study were to assess the library user satisfaction regarding the currently available information sources and services and to identify the unmet needs of the undergraduates for the future developments in the library. Self administered questionnaire survey was conducted among these undergraduates. The study revealed that the library retains as essential component to facilitate the general degree bioscience undergraduates’ learning and research activities. The study clearly enumerated that the efficiency of some of the presently available services such as photocopying services, interlibrary loan services, selective dissemination of information and current awareness service were not met the undergraduates’ expectations. . The findings of the survey leave plenty of scope for improvement in library activities.
Keywords: User satisfaction; User surveys; Academic libraries; User needs